Apricot fruit chilling injuries during the cold storage affected by harvest maturity - Ezzat, A. (International Journal of Horticultural Science, 2019)
The study aimed to find the effect of different maturity classes (up to the days after full blossom) on the post-harvest life of 3 different apricot varieties Gold Cot, Bergarouge and Flavor Cot in Hungary. The fruit harvested in a particular time 65, 75 and 85 days after full blossom and divided to three maturity classes (Class 1, 2 and 3, respectively). Fruit stored in cold storage for 7 days at temperature 1 °C. Fruits were investigated in regard to physical parameters (weight loss, fruit firmness and soluble solid content SSC) and chilling injuries. The results showed that the varieties followed different ways in regard to response to different maturity classes. The maturity class I for all the tested varieties recorded the lowest weight loss, while with the increasing maturity stage the weight loss percentage for all the varieties recoded high values. The firmness decreased with delayed harvesting for all the varieties. Data of the chilling injuries showed that all the fruits which harvested at maturity I, recorded the highest percentage of fruit with CI (chilling injuries) at 0 (48.5, 37.25 and 38.75%) and CI class I (44.75, 35.75 and 39.75%) for Bergarouge, Gold Cot, and Flavor Cot.